Where and when are dislocations induced by thermal cycling in Ti–Ni shape memory alloys?. (1st January 2023) - Akamine, H.; Heima, A.; Soejima, Y.; Mitsuhara, M.; Inamura, T.; Nishida, M.
Abstract: Systematic experiments were performed to determine where and when dislocations are induced during the thermal cycling of Ti–Ni shape memory alloys. The decrease in transformation temperatures upon thermal cycling became less pronounced with increasing Ni concentration, which was supported by the dislocation densities estimated from scanning transmission electron microscopy observations. The arrangement of transformation-induced dislocations after the 1st thermal cycle reproduced the self-accommodation structure of B19ʹ martensite. Three-dimensional visualization revealed that the complex spiral appearance of the dislocations after the 1st thermal cycle was attributable to the duplicated projection of relatively simple elongated dislocation loops aligned in the depth direction parallel to 〈111〉B2 along {110}B2 . No dislocations were observed along the twin boundary in the initially transformed martensite, whereas there were numerous dislocations parallel to the trace of the {110}B2 planes in the martensite formed upon the 2nd thermal cycle. The results suggest that the transformation-induced dislocation loops were generated during the reverse transformation rather than the forward transformation. The possible source site of the transformation-induced dislocations is also discussed. Graphical abstract: Image, graphical abstract